Identification and Pathogenicity of a New Entomopathogenic Fungus, Mucor hiemalis (Mucorales: Mucorales), on the Root Maggot, Bradysia odoriphaga (Diptera: Sciaridae). Issue 2 (18th March 2022) - Zhu, Guodong; Ding, Wenjuan; Xue, Ming; Zhao, Yongfei; Li, Mingzhu; Li, Zizheng
Abstract: Bradysia odoriphaga Yang and Zhang (Diptera: Sciaridae), the Chinese chive root maggot, is a destructive pest of Allium vegetables and flowers that causes severe losses in northern China. Novel biological control technologies are needed for controlling this pest. We identified a new entomopathogenic fungus isolated from infected B. odoriphaga larvae and evaluated the susceptibility of the biological stages of B. odoriphaga and the effects of temperature on fungus growth and pathogenicity. Based on morphological characteristics and molecular phylogeny, the fungus was identified as Mucor hiemalis BO-1 (Mucorales: Mucorales). This fungus had the strongest virulence to B. odoriphaga larvae followed by eggs and pupae, while B. odoriphaga adults were not susceptible. A temperature range of 18–28°C was optimum for the growth and sporulation of M. hiemalis BO-1 and virulence to B. odoriphaga larvae. At 3 and 5 d after inoculation with 10 5 spores/ml at 23°C, the survival rates were 24.8% and 4.8% (2nd instar larvae), respectively, and 49.6% and 12.8% (4th instar larvae), respectively. The potted plant trials confirmed that M. hiemalis BO-1 exerted excellent control efficiency against B. odoriphaga larvae, and the control exceeded 80% within 5 d when the spore concentration applied exceeded 10 7 spores/ml. In conclusion, these findings supported the hypotheses that this fungus could serve as an effective control agent against B. odoriphaga larvae and is worth being further tested to determine its full potential as a biocontrol agent. Graphical Abstract: